The Application of Lake Sediments for Climate Studies - Mishra, Praveen K. (Cham : Springer International Publishing : Imprint: Springer, 2023)
The book discusses a comprehensive overview of various limnological approaches for climate studies, and sheds light on a multi-dimensional approach (i.e., field, laboratory, and data analysis; modern investigations; proxy development/calibration; proxy interpretation; and validation of climate models with proxy data) for climate reconstruction. The study highlighted the utilization of lake sediment as an archive for paleoclimate research. With the help of several case studies from around the globe (Israel, India, Turkey, Kyrgyzstan, Tibet, China and Europe), this brief provides a unique way to understand the implication of the methodological framework for climate studies. The book emphasizes the importance of field-based modern investigations to establish baseline characteristics of lake basins according to changes in environmental conditions. It also unveils the role of paleoclimate studies in climate model validation to forecast future climate variability. The book is a valuable resource for early career researchers interested in climate studies especially those using lake sediments as climate archive.
Chapter 1-Lake sediments and climate studies -- Chapter 2- Working approach: Field investigation -- Chapter 3- Working approach: Lab investigation and proxy development -- Chapter 4- Proxy response in various climatic conditions -- Chapter 5- Summary and Future scope.
Keywords: Earth sciences; Climatology; Sedimentology; Water; Hydrology; Earth Sciences; Climate Sciences; Sedimentology; Water